Impact of service quality, brand image, perceived value, customers’ satisfaction and behavioural intentions in the traditional retailing in the North of Portugal - Veloso, Cláudia M. (2017)
In the service sector mainly in the traditional retailing, customers and the employees are key actors in service interplay. The quality and performance of any service are dependent on customer expectations and the efficiency the company is able to serve its customers. The crucial point of customer satisfaction is to identify the important attributes, considered by customers as their needs and expectations. The purpose of this study is to suggest the adaptation of SERVQUAL in evaluating the perceived quality of service offered by traditional retailing, namely in traditional retail stores in the North Region of Portugal. The proposed conceptual model aims to analyse if: (1) perceived service quality (five dimensions of SERVQUAL) directly contribute to customer satisfaction, customer-perceived value and brand image; (2) brand image and customer-perceived value directly contribute to customer satisfaction; (3) brand image directly contribute to customer-perceived value; (4) customer satisfaction directly influences the intention to return and WOM recommendation (Word-of-Mouth communication intention); and (5) the intention to return has a direct impact on WOM recommendation. This research is of particular interest to the literature on the retailing and to the practitioners, since there are few studies in this field which apply to the Portuguese traditional retailing.